Ecological and behavioural drivers of offspring size in marine teleost fishes. Issue 12 (18th September 2021) - Vanadzina, Karina; Phillips, André; Martins, Bonnie; Laland, Kevin N.; Webster, Michael M.; Sheard, Catherine
Abstract: Aim: Our aim was to evaluate the role of ecological and life‐history factors in shaping global variation in offspring size in a marine clade with a diverse range of parental care behaviours. Location: Global. Time period: Data sourced from literature published from 1953 until 2019. Major taxa studied: Marine teleost fishes. Methods: We compiled a species‐level dataset of egg and hatch size for 1, 639 species of marine fish across 45 orders. We used Bayesian phylogenetic mixed models to evaluate the relationship between offspring size and environmental factors (i.e., mean temperature, chlorophyll‐ a and dissolved oxygen content together with their annual variation), as well as latitude, reproductive strategy, parental body size and fecundity. We also tested long‐standing hypotheses about the co‐evolution of offspring size and the presence of parental care in BayesTraits . Results: After controlling for parental body size and phylogenetic history, we find that increased egg size is associated with colder and oxygen‐rich waters, while hatch size further depends on food supply and the reproductive strategy exhibited by the species. Irrespective of the initial investment in egg size, species with parental care or demersal egg development yield larger hatchlings compared to pelagic spawners. We also demonstrate that hatch size has co‐evolved with advanced forms of care in association with parental body but fail to find a relationship with other types of care. Main conclusions: Our study shows that parental care behaviours, together with environmental context, influence the evolution of classic life‐history trade‐offs on a global scale. While the initial investment in eggs is driven primarily by temperature and oxygen content, hatch size also reflects the impact of care an offspring has received throughout development. In support of the 'offspring‐first' hypothesis, we find that an increase in hatch size drives the evolution of advanced care provision.